Peranan Infrastruktur Jalan Terhadap Perekonomian Regional Di Indonesia - Maimunah, Siti (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
During the development stage, provision of transportation infrastructure is ven; important. It contnbutesto the regional economy and makes economic development more inclusive by giving directand indirect effects. The aim of research wants to know the role of road infrastructure to regionaleconomy in long term periods.Having panel data in the regional level (province) which is 26 provinces and a 14-year time series(1993-2006), variables that are used in this stud!; are GDP as the output measurement, labor forceand capital stock which is divided into road capital stock and non road capital stock. Road capitalstock itself is comprised of national, province and city road capital stock.Based on the model in analysis, we can say road infrastructure has significant contributions to theregional econonn; where city roads give the highest contnbution to the regional econonn;. In addition,based on the time lag model, we can see that the investment in road development will have a significanteffect on GDP in the curre11t year, as well as in the following .few years, but the effect diminishesover time. However, the significant contnbution of road development to GDP only remains for 1 yearfor all types of road.Some polictj implications that can be proposed from the above analysis are: it is still necessary toincrease the development of road infrastructure in order to provide good accessibility for all regions inIndonesia; so government should give priorihJ to develop city and province roads rather than nationalroads to increase the regional output (regional GDP). On the other hand government shouldmake it a priority to develop strategies for the development of road infrastructure based on the specificneeds of each region so it will be more effective and efficient in encouraging regional economic growthand, ultimately, in enhancing high economic growth in Indonesia as a whole.Key words: road infrastructure, regional econonn1